Pelatihan Pra Bencana untuk Membentuk Desa Tanggap Bencana di Desa Sumberbrantas Jawa Timur - Edi Widianto; Fikri Firdaus; Salma Isna Afifa; Ananda Nazilla; Elok Dinda; Nurul Fitriani; Hanik Ainun Nisak (Universitas Mathla'ul Anwar Banten, 2021)
PRE-DISASTER TRAINING TO ESTABLISH DISASTER RESPONSE VILLAGES IN SUMBERBRANTAS VILLAGE, EAST JAVA. A disaster is an event that can interfere with human survival, disasters appear due to natural or human factors. Based on some of the data obtained, there are several problems which are described as follows: (1) Do not care about the environment; (2) lack of knowledge regarding pre-disaster preparation; (3) do not know the principle of disaster preparedness; (4) do not know first aid that must be done to oneself or others. This group will collaborate with SDN 03 Telungrejo. This training is intended to establish a disaster response village in the village of Sumberbrantas. The target of training participants is elementary school children who will be given knowledge about disasters and how to deal with when a disaster occurs. The purpose of this training is to form training participants who are ready to face unexpected disasters. The methods and techniques in this training are lectures, questions and answers, demonstrations and simulations. The facilitator for this training is BPBD Kota Batu.